Spectral Overlays for Reading Difficulties: Oculomotor Function and Reading Efficiency Among Children and Adolescents With Visual Stress. Issue 2 (April 2020) - Guimarães, Márcia Reis; Vilhena, Douglas de Araújo; Loew, Stephen J.; Guimarães, Ricardo Queiroz
This study analyzed the effects of spectral overlays on ocular motility during reading among a clinical group of children and adolescents experiencing visual–perceptual distortions of text. We reviewed the records of 323 eye-hospital patients diagnosed with visual stress and divided this participant sample into two age-based cohorts: children ( n = 184; Mean [ M ] age = 10.1, standard deviation [ SD ] = 1.3 years) and adolescents ( n = 139; M age = 14.6, SD = 1.5 years). We used a Visagraph III Eye-Movement Recording System to record ocular motor efficiency while reading with and without spectral overlays, and we examined the following parameters: (a) Fixations, (b) Regressions, (c) Span of Recognition, (d) Reading Rate, (e) Relative Efficiency, and (f) Comprehension. Our results showed that using one or some combination of 10 participant-selected spectral overlays immediately and significantly ( p < .001) reduced the number of Fixations and Regressions per 100 words, while there were significant ( p < .001) gains in positive factors such as Span of Recognition, Reading Rate, Relative Efficiency, and Comprehension. Our findings indicate that spectral filtering can be an effective tool for helping many young patients who experience visual–perceptual distortions while reading. Future expanded research employing eye-tracking technology is clearly needed.